2017
DOI: 10.1504/ijcee.2017.080635
|View full text |Cite
|
Sign up to set email alerts
|

An augmented Taylor rule for the Federal Reserve's response to asset prices

Abstract: This paper investigates whether and how the US Federal Reserve has reacted to asset price developments over the period 1979-2011. We examine both the opportunities and limitations of incorporating two asset prices, equity and real estate, into a standard forward-looking and inertial interest rate rule, based on ex-post realised monthly data and taking into account the inherent endogeneity. While the role of house prices is found to be ambiguous due to weak identification, stock prices do represent an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The a priori expectation is a negative and significant coefficient with a value close 0.5 in the CFCI parameter, in accordance with the literature (Hafner and Lauwers 2017;Nair and Anand 2020). The value of 0.5 implies that the SARB can lean against the wind by targeting the aggregate FC as a fully flagged objective, while lower values indicate targeting the FC only as a genuine augmentation.…”
Section: A Finance Augmented Taylor Rule Modelsupporting
confidence: 86%
See 3 more Smart Citations
“…The a priori expectation is a negative and significant coefficient with a value close 0.5 in the CFCI parameter, in accordance with the literature (Hafner and Lauwers 2017;Nair and Anand 2020). The value of 0.5 implies that the SARB can lean against the wind by targeting the aggregate FC as a fully flagged objective, while lower values indicate targeting the FC only as a genuine augmentation.…”
Section: A Finance Augmented Taylor Rule Modelsupporting
confidence: 86%
“…In accordance with Hafner and Lauwers (2017), the wide applicability of the original Taylor rule model came from its simplicity, intuitiveness, and its realism. However, this original version became slightly outdated as it was based on the assumptions that the central bank is backward-looking and trails on the non-inertial policy rule.…”
Section: The Original Taylor Rule Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, explorations on the role of exchange rates on the monetary transmission mechanism have been conducted by, among others, Taylor (2001), and Froyen and Guender (2018). Whilst studies by Bernanke and Gertler (2000), and Hafner and Lauwers (2015), among others, have investigated the central banks' responses to asset price movements. Furthermore, Taylor and Williams (2010) suggested that the exploration of alternative policy rules may need to involve the international linkages of monetary policy and the economies.…”
Section: Introductionmentioning
confidence: 99%